2017
DOI: 10.1007/s12519-017-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon α/ribavirin therapy enhances bone mineral density in children with chronic genotype 4 HCV infection

Abstract: Low BMD is detectable in a proportion of CHC children. Antiviral therapy leads to a sustainable increase in BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…82 Overall, there have been eleven clinical trials (1 randomized and 10 open-label) on the use of pegylated interferon (PEG IFN) in adolescents and children less than 12 years. [92][93][94][95][96][97][98][99][100][101][102] In genotype 1, the SVR of PEG IFN and ribavirin was suboptimal compared to DAA, with an SVR of only 52% in those with HCV genotype 1 and 4, but 89% in genotypes 2 and 3. 82,103 PEG IFN and ribavirin are associated with significant side effects during treatment, and potentially irreversible after-therapy side effects, such as thyroid disease, type 1 diabetes, ophthalmological complications and growth impairment.…”
Section: Antiviral Treatment and Indications For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Overall, there have been eleven clinical trials (1 randomized and 10 open-label) on the use of pegylated interferon (PEG IFN) in adolescents and children less than 12 years. [92][93][94][95][96][97][98][99][100][101][102] In genotype 1, the SVR of PEG IFN and ribavirin was suboptimal compared to DAA, with an SVR of only 52% in those with HCV genotype 1 and 4, but 89% in genotypes 2 and 3. 82,103 PEG IFN and ribavirin are associated with significant side effects during treatment, and potentially irreversible after-therapy side effects, such as thyroid disease, type 1 diabetes, ophthalmological complications and growth impairment.…”
Section: Antiviral Treatment and Indications For Treatmentmentioning
confidence: 99%
“…82,103 PEG IFN and ribavirin are associated with significant side effects during treatment, and potentially irreversible after-therapy side effects, such as thyroid disease, type 1 diabetes, ophthalmological complications and growth impairment. [92][93][94][95][96][97][98][99][100][101][102] In clinical practice, IFN treatment has been mainly limited to the few children with persistently elevated serum aminotransferases, progressive liver disease (i.e. fibrosis on liver histology) or HIV coinfection, 104 while for most children, follow up without treatment until adulthood has been preferred.…”
Section: Antiviral Treatment and Indications For Treatmentmentioning
confidence: 99%
“…The schematic of study selection process is provided in Figure 1, whereas the complete results of the searches are described in the Appendixes 2 to 5 (Supplemental Digital Content, http:// links.lww.com/MPG/B238). Overall, 16 studies met the inclusion criteria (35)(36)(37)(38)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The inter-rater reliability for study inclusion was high (f ¼ 1).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have included usually samples of less than 50 patients treated with peginterferon plus ribavirin regimens. Although limitations of these studies are evident, they have demonstrated that BMD values at the lumbar spine and the femoral neck improve after the treatment[ 146 , 147 ], but controversial data have been also reported[ 148 ].…”
Section: Effects Of Svrmentioning
confidence: 99%